Hubungan Komunikasi Interpersonal dengan Orang Tua dan Keterbukaan Diri pada Mahasiswa Fakultas Psikolog Universitas Negeri Makassar - Abadi, Siti Hariyanti; Firdaus, Faradillah; Nurdin, Muhammad Nur Hidayat (Madani: Jurnal Ilmiah Multidisiplin, 2024)
An individual's self-disclosure can be influenced by various things, one of which is interpersonal communication. This study aims to see whether there is a relationship between interpersonal communication with parents and self-disclosure in students of the Faculty of Psychology, Makassar State University. Respondents in this study numbered 323 people with the criteria of students of the Faculty of Psychology, Makassar State University. The measuring instrument used in this study was the scale of interpersonal communication and self-disclosure. The data in this study were analyzed using the Spearman Rho test. The results of the data analysis showed a significance value of 0.001, meaning that there is a relationship between interpersonal communication with parents and self-disclosure. The r value obtained was 0.12, indicating that interpersonal communication with parents has a positive relationship with students' self-disclosure. The implications of this study are that it can contribute to the development of knowledge related to interpersonal communication with parents and self-disclosure, and be used as a guideline for students and parents.